KOMUNIKASI INTERPERSONAL ORANG TUA DALAM PENGGUNAAN GADGET PADA ANAK USIA DINI DI KAMPUNG UTAN JATI KALIDERES JAKARTA BARAT - OKTAVIANI, KOVIFAH; PURWANTO, EKO; KHAERIAH, ADE SITI (Universitas Muhammadiyah Tangerang, 2023)
Tujuan penelitian ini adalah Untuk melngeltahuil komunilkasil interpersonal orang tua dalam pelnggunaan gadgelt pada anak usila dilnil dil Kampung Utan Jatil dan Untuk melngeltahuil faktor pelnghambat orang tua dalam pelnggunaan gadgelt pada anak usila dilnil dil Kampung Utan Jatil. Dalam penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data yang digunakan ialah ialah wawancara, dokumentasi, dan observasi. Untuk menguji keabsahan data, penenlitian ini menggunakan teknik analisis data yaitu triangulasi. Hasil penenlitian ini menunjukkan bahwa Komunikasi Interpersonal yang dilakukan oleh orang tua kepada anak usia dini saat menggunakan gadget berjalan baik dalam keseharian di keluarga. Dapat dilihat dari 5 keefektifan teori Devito yang di mana anak diajarkan untuk menjadi pribadi yang terbuka, orang tua berempati dengan anak saat menggunakan gadget, sikap positif orang tua yang bisa dicontoh oleh anak, sikap mendukung orang tua usia dini dalam mengatur penggunaan gadget pada anak, dan juga kesetaraan antara orang tua dengan anak saat mengunakan gadget.Kata kunci: Komunikasi Interpersonal, Penggunaan Gadget, Anak Usia DiniAbstractThus interpersonal communication that occurs between parents and early childhood in the use of gadgets in Kampung Utan Jati, Kalideres, West Jakarta, where children aged 1-6 years are a golden period that still requires parents to care for and look after them, especially when using children's gadgets. must be accompanied. The purpose of this study was to find out the interpersonal communication of parents in the use of gadgets in early childhood in Kampung Utan Jatil and to find out the inhibiting factors of parents in the use of gadgets in old age children in Kampung Utan Jatil. In this study using qualitative methods. Data collection techniques used are interviews, documentation, and observation. To test the validity of the data, this research uses a data analysis technique, namely triangulation. The results of this study indicate that Interpersonal Communication carried out by parents with early childhood when using gadgets goes well in everyday life in the family. It can be seen from the 5 effectiveness of Devito's theory where children are taught to be open individuals, parents empathize with children when using gadgets, positive attitudes of parents that can be emulated by children, attitudes of supporting parents at an early age in managing the use of gadgets in children, and also equality between parents and children when using gadgets.Keywords: Interpersonal Communication, Use of Gadgets, Early Childhoo